2020
DOI: 10.1093/cid/ciaa200
|View full text |Cite|
|
Sign up to set email alerts
|

A Case of 2019 Novel Coronavirus in a Pregnant Woman With Preterm Delivery

Abstract: We presented a case of a 30-week pregnant woman with COVID-19 delivering a healthy baby with no evidence of COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
429
3
51

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(519 citation statements)
references
References 10 publications
21
429
3
51
Order By: Relevance
“…So far, few reports have provided information on the clinical and imaging follow up of pregnant patients with COVID-19. Although, no mortality has been reported among their patients [4][5][6].…”
Section: Introductionmentioning
confidence: 95%
“…So far, few reports have provided information on the clinical and imaging follow up of pregnant patients with COVID-19. Although, no mortality has been reported among their patients [4][5][6].…”
Section: Introductionmentioning
confidence: 95%
“…There is no evidence that the virus can be transmitted vertically from the mother to the fetus during pregnancy. This is based on; one study of 9 pregnant women with laboratory-confirmed COVID-19 pneumonia [8];a single case report [9]; a study of 41 pregnant women with confirmed COVID-19 [11]; and a study of 15 pregnant women with COVID-19 [10].…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Actuellement il a été publié deux cas de femmes enceintes ayant nécessité une ventilation mécanique à 30 SA (semaines d'aménorrhée) et 34 SA (7,14) avec réalisation d'une césarienne compte tenu de l'état maternel et aucun décès n'a été rapporté chez une femme enceinte (Dans l'étude de Liu et al (7), la patiente était encore en ECMO au moment de la rédaction de l'article).…”
Section: Chez La Femme Enceinteunclassified